2021
DOI: 10.1111/ijlh.13717
|View full text |Cite
|
Sign up to set email alerts
|

New insights into genetic characteristics between multiple myeloma and COVID‐19: An integrative bioinformatics analysis of gene expression omnibus microarray and the cancer genome atlas data

Abstract: Background Multiple myeloma (MM) is a hematological malignancy. Coronavirus disease 2019 (COVID‐19) infection correlates with MM features. This study aimed to identify MM prognostic biomarkers with potential association with COVID‐19. Methods Differentially expressed genes (DEGs) in five MM data sets (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE47552, http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE16558, http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE13591, http://www.ncbi.nlm.nih.gov/geo/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Zmorzyński et al 23 found that the NOD2/CARD15 variant (3020insc) and PS6 polymorphism affect the occurrence and prognosis of MM. New insights into the genetic characteristics by Wang et al 24 between MM and COVID-19 showed that NOD2 and COX6C genes could be used as prognostic biomarkers for MM. These studies suggest that there is a correlation between pyroptosis-related genes and MM, which affects the occurrence and development of MM and may provide evidence for exploring the unknown mechanism of MM.…”
Section: Introductionmentioning
confidence: 99%
“…Zmorzyński et al 23 found that the NOD2/CARD15 variant (3020insc) and PS6 polymorphism affect the occurrence and prognosis of MM. New insights into the genetic characteristics by Wang et al 24 between MM and COVID-19 showed that NOD2 and COX6C genes could be used as prognostic biomarkers for MM. These studies suggest that there is a correlation between pyroptosis-related genes and MM, which affects the occurrence and development of MM and may provide evidence for exploring the unknown mechanism of MM.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of multiple myeloma prognostic biomarkers and potential association with COVID-19, differentially expressed genes were identified, including NOD2 gene as an independent factor related to disease prognosis. NOD2 gene was downregulated in patients with mild COVID-19 infection compared with controls but was upregulated in patients with severe COVID-19 compared with patients with mild illness [ 42 ]. In a murine study, MDP treatment of Influenza A virus infected animals significantly reduced mortality, viral load, and pulmonary inflammation in a NOD2-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…COX6C gene encodes component of the cytochrome c oxidase, the last enzyme in the mitochondrial electron transport chain which drives oxidative phosphorylation. COX6C is differentially expressed in multiple myeloma (MM) and is associated with MM prognosis ( 44 ). Multiple myeloma (MM) is a malignant proliferation of plasma cells, with the coexistence of a monoclonal component (M-component) plus impairment of normal immunoglobulin production, which are associated with increased risk of viral and bacterial infections ( 45 ).…”
Section: Discussionmentioning
confidence: 99%